A comparative account of resistance and antagonistic activity of healthy and bleached coral-associated bacteria as an indicator of coral health status - Neha P. Patel (Elsevier, 2021)
Bacteria have proven its worth as a bioindicator in many fields. Therefore, the characterization of native coral bacteria is essential as they could be used as an indicator of coral health status. For this, bacteria are isolated from the healthy and bleached state of two dominant corals (Porites spp. and Turbinaria spp.) collected in the winter and summer seasons from the Gulf of Kutch (GoK), Gujarat, India. These isolates are evaluated for their antibiotic resistance (AR) and antagonistic activity as these bacterial properties are important to compete with the host and other microbes for nutrients and space on the coral surface. The average multiple antibiotic resistance (MAR) index on the healthy coral surface (0.20 ± 0.01) is more compared to the MAR on the bleached coral surface (0.18 ± 0.01) suggesting the microbes on healthy coral surface has high AR ability. Similarly, the MAR index in summer (0.21 ± 0.01) is higher than the MAR index in winter (0.17 ± 0.01) season indicates an increase in the microbial load and competition with the increase in sea surface temperature (SST). Porites spp. (0.20 ± 0.02) have slightly more MAR than Turbinaria spp. (0.19 ± 0.01). Further, isolates with high MAR index are selected for antagonistic assay and overall results suggest that the antagonistic activity of bacteria from the healthy coral surface (83%) are slightly more compared to the isolates from bleached coral surface (78%). The AR profile and antagonistic activity of bacteria associated with corals would be helpful for preliminary screening of native or pathogenic bacteria of corals, which could be used as the indicator of coral health status or could form the basis for developing quantitative tools for predicting the coral health status.